The evolution of corruption theories as a prerequisite for the formation and implementation of state criminal law policy - Lukashuk, Oksana (Public Policy and Accounting, 2024)
Corruption is a complex socio-economic phenomenon that significantly harms the efficiency of state institutions and social development. It undermines democratic governance and the rule of law, inhibits economic growth, distorts market competition and causes citizens to distrust government. Understanding its mechanisms through the prism of different theoretical approaches allows for the formation of a holistic anti-corruption strategy. The article analyzes the evolution of key theories of corruption - from classical models of the principal-agent and collective action to modern institutional, network and rational-choice concepts. The main mechanisms are identified by which each of these theories justifies corrupt behavior as a consequence of certain economic, social and institutional factors. It is clarified how the achievements of the study of each of these theories can be integrated into the creation of effective measures of state criminal law policy to prevent and combat corruption. Practical recommendations for improving the public administration system have been developed, which will be based on a synthesis of the analyzed theoretical approaches. Each of these theories reveals unique aspects of corruption phenomena, which together create the basis for systemic counteraction through legislative, institutional, and social mechanisms.